2013
DOI: 10.1016/j.econmod.2013.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Geographical simulation analysis for logistics enhancement in Asia

Abstract: This paper presents a simulation of the reduction of several components in trade cost for Asia and examines its impact on the economy. Our simulation model based on the new economic geography embraces seven sectors, including manufacturing and non-manufacturing sectors, and 1,715 regions in 18 countries/economies in Asia, in addition to the two economies of the US and the European Union. The geographical course of transactions among regions is modeled as determined based on firms' modal choice. The model also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Other simulation-based studies have also found an uneven distribution of economic benefits along transport corridors, such as the Dhaka-Kolkata corridor in Bangladesh [14], and the Delhi Mumbai Industrial Corridor (DMIC) in India [67].…”
Section: Location and Spatial Effectsmentioning
confidence: 99%
“…Other simulation-based studies have also found an uneven distribution of economic benefits along transport corridors, such as the Dhaka-Kolkata corridor in Bangladesh [14], and the Delhi Mumbai Industrial Corridor (DMIC) in India [67].…”
Section: Location and Spatial Effectsmentioning
confidence: 99%
“…IDE/ERIA‐GSM explicitly incorporates land size in its production size and keeps its technology as constant returns to scale. Details of the IDE/ERIA‐GSM are provided in Kumagai et al ().…”
Section: Geographic Simulation Modelmentioning
confidence: 99%
“…In light of these developments, this paper examines the importance of transportation infrastructure developments by comparing the economic impacts of MPAC and CADP for ASEAN using the Geographical Simulation Model (Institute of Developing Economies/ERIA‐GSM), which has been developed by the IDE‐JETRO and ERIA since 2007. IDE/ERIA‐GSM is a tool to help policymakers comprehend the importance of infrastructure provision and its potential consequences (Kumagai et al, ). The model can predict the type of physical or institutional integration that favorably or adversely affects a particular region(s) at the subnational level.…”
Section: Introductionmentioning
confidence: 99%
“…Source: Kumagai et al (2011) GSM includes the average speed of each transport mode based on survey results of ERIA's innovation and agglomeration projects (Limskul 2009 andIntarakumnerd 2010) and the ASEAN Logistics Network Map by JETRO (JETRO 2008 and). The basic speed of land transport is set at 38.5 km/h.…”
Section: Figure 2: Basic Structure Of the Simulation Modelmentioning
confidence: 99%